Análise sobre a articulação da rede de proteção acerca de casos de violência sexual: percepção dos profissionais envolvidos - Faustino, Shirlei Mendes (2022)
Sexual violence perpetrated against children and adolescents is a public health problem, given the prevalence of this type of violence. It affects children of all social statuses, and has a higher incidence within the family. Protecting these children from any type of violation of their rights is the task of a network of services, which, when well structured, can achieve the objectives of combating violence. This work proposes to analyze the importance of welcoming and protection networks for the referral of cases of violence. The main objective is to identify how the protection network against violence against children and adolescents should be articulated, in the perception of its actors. Outlined as a cross-sectional research with a qualitative approach, the study was guided by national and international documents that guide how to promote prevention and care for cases of sexual violence, greater appropriation of national laws, aiming at a greater understanding of how the protection network needs to be articulated. As the Rights Guarantee System is very extensive, it was decided to dialogue through semi-structured interviews with a few services, namely: the Tutelary Council, CREAS, the Assistance Program for Victims of Sexual Abuse (PAVAS) and the Commission for Organizing the Flow of Violence in the municipality of São Carlos. The analysis of the interviews departed from the inspiration of Foucault's Genealogy, seeking to identify possible statements involved in power relations. The results demonstrate a need for greater intersectoral articulation, as well as the accountability of some actors. The lack of technical training and few alignments also appear as negative factors. The non-discursive practices that were evidenced refer to power relations, the result of a culture of violence, to which this protection network is subordinated.